(untitled) (Colombia Medica, 1990)
The symptoms, clinical manifestations, and surgical approach of 31 patients with rectal prolapse are described. There were 27 overt rectal prolapses, and 4 were occult rectal prolapses. Rectal protrusion, bleeding, defecatory obstruction and mucorrhea were the most common symptoms. In patients with complete rectal protrusion, diagnoses were made by physical examination. Endoscopy plus defecography gave important additional information in cases with overt manifestations; besides, they made the diagnosis when prolapses were occult. Additionally, defecography was helpful in post-operatory control. All patients were treated either by anterior rectopexy (Reipstein’s technique), 17 cases, or by posterior rectopexy (Well’s procedure), 15 cases. After anterior rectopexy, two recurrences occurred, and both methods were applied to one of the patients.